Perceptions of shared decision-making participation during cardiac rehabilitation in coronary heart disease patients after coronary artery bypass surgery grafting: a qualitative study - Hang Wang; Meng Xiu; Fei Yang; Meijie Zhang; Chenwei Wang; Qi Wang; Yuhan Cheng; Xue Liu; Weiying Zhang (BMC Cardiovascular Disorders)
Abstract Background Cardiac rehabilitation is a widely adopted approach for postoperative recovery in coronary heart disease patients undergoing coronary artery bypass grafting (CABG). However, in China, patients tend to be highly dependent on medical staff and less expressive of their personal wishes in medical decision-making due to the influence of traditional concepts. This study aims to investigate the current status of CABG postoperative patients' perceptions of shared decision-making during cardiac rehabilitation. Methods Using the Colaizzi’s phenomenological method, 19 post-CABG from three tertiary general hospital in Shanghai were purposively selected for semi-structured in-depth interviews between February 2025 to April 2025. Results Two main themes and eight subthemes emerged: (1) Patients’ perceptions of SDM participation during cardiac rehabilitation, including insufficient understanding of the role, restricted decision-making capacity, impact of medical staff-patient communication quality, and psychological barriers to engagement; (2) Patients’ needs for shared decision-making participation during cardiac rehabilitation, knowledge requirements for cardiac rehabilitation, continuity of medical resources, family support, and decision aids. Conclusion Post-CABG patients exhibit limited awareness of shared decision-making and face multifaceted barriers to participation. Future interventions should enhance patients’ decision-making awareness and address their needs through education, resource continuity, family engagement, and tailored decision aids to improve rehabilitation adherence and quality of life.